Estudio de prefactibilidad para la instalación de una planta productora de dips a base de quinua y vegetales verdes - Acosta Llaury, Carlos Javier (2018)
The present study seeks to determine the prefeasibility for the installation of a quinoa and green vegetables dips manufacturing plant. This product plans to develop an unattended market and take advantage of one of the main trends: healthy consumption. In the first three chapters, the general aspects are mainly fixed as: the objectives, scope, limitations and hypothesis of the investigation; In addition, a market study was carried out with which 807 274 units of 180 gr were determined as objective demand for the first year in SES (Socioeconomic Status) A and B of sixth and seventh Lima zones. Also, after the analysis of pair-wise ranking, Trujillo was chosen as the optimal location for operations. During chapter IV, it can be verified that there are no limitations for the project about technology and resources. However, critical market variables lead to the conclusion that the optimum plant size for 2022 is 1 014 406 units. Chapter V, key in the development of the investigation, shows in detail the engineering of the project. Through DOP, Relational Diagram and Guerchet method, the minimum required area was calculated and the plant layout was defined. Finally, chapters VI, VII and VIII analyze the economic and financial viability of the Cash Flow, Balance Sheet and Income Statement. Obtaining, from an investment of S /. 1 819 507, a NPV (Net Present Value) of S /. 918 065, IRR (Internal Rate of Return) of 80.11% higher than Opportunity cost and a recovery period after 1 year and 10 months. Finally, in chapter IX, the social impact of the project will be evaluated.